Urgensi Ijtihad Dan Peranannya Dalam Menjawab Problematika Ekonomi Modern - Dini Anggreini Khairunnisa; Muhajirin Muhajirin (FEB Universitas Muhammadiyah Jakarta, 2023)
The foundations of Islamic law are the Quran, Hadith, Ijma' and Qiyas, where their existence is the foundation of life and solutions to human problems. The editorials of the Qur'an and al-Sunnah are very limited. It is almost agreed that the verses relating to economic law and material relations or mu'amalah are only 80 verses, 1.28% of all the verses of the Quran. While in general, the hadiths that discuss law range from 4500 pieces. This implies the need for ijtihad as a solution to solving new problems that arise in society. For a Muslim in modern times, there's a lot of new issues brought on by developments should not be solved in a convensional way but instead through Ijtihad. The evidence demonstrates that society and public opinion are developing more quickly than the legislation itself. One aspect of change is the dynamics of community life. As a result of their works, humans produce cultural objects through intention, power, and creativity.. This paper examines how ijtihad has become something important for today's economy, one of the most discussed topics in society, because economic development, especially Islamic economics, is conceptually and practically so massive and dynamic. This research uses library research through content analysis techniques, with the results of the development of a dynamic Islamic economic sector. The existence of ijtihad can be a kind of positive response to the need for a legal basis for Islamic economic or commercial activities. In Indonesia, there are some existence of fatwas in the field of sharia economics, which is by DSN MUI, accompanied by several examples of problems such as sharia banking, delivery order services on online applications, services on social media platforms and the application of debt agreements.